Housing Crocodilians in Captivity: Considerations for Central America and Caribbean - Matthew L. Brien; Michael S. Cherkiss; Mark W. Parry; Frank J. Mazzotti (EDIS)
Circular 1513, a 26-page illustrated circular by Matthew L. Brien, Michael S. Cherkiss, Mark W. Parry, Frank J. Mazzotti, provides information for facility planning, species selection, housing, safety, water quality and maintenance, heating and thermoregulation requirements, diet and feeding, captive breeding and rearing. Includes bibliography and references. Published by the UF Department of Wildlife Ecology and Conservation, February 2007.